ANALYSIS OF FEMINISM IN THE NOVEL OF LITTLE WOMEN BY LOUISA MAY ALCOTT - Desmawati, Eka (Journal of Language and Literature, 2018)
Women’s movement is in order to reach the equality of right with men in many aspects, such as politic, social, economy and culture. Everyone should be treated as equals unless special circumstances apply regardless of the role of men or women. The problem undertaken in this research relate to feminism, specifically on types of feminism within the female characters in the novel and the reflection of the feminism itself in the ongoing developments of the characters.  The aims of the research are to elaborate types of feminism and their reflection on feminism in novel little women. This research used a qualitative descriptive method and the source of data taken from Little Women novel. As the result of the research, it described that there are four types of feminism from the novel little women. The characters in the novel reflected in Liberal feminism, Marxist feminism, Existentialist feminism, and Radical feminism. However, Feminism is reflected by the struggle of the characters in survival, in placing these lives in the world of men (patriarchy), in being comfort with themselves to do what they feel comfortable for her, as well as their protest form to no longer be the object of violence for men